A new species and a key to 10 species of the genus Lemba Huang, 1983 (Orthoptera: Catantopidae) from China - Yin, Hai-Xiang; Shen, Wei-Xing; Yin, Zhan (Zootaxa, 2020)
A new species and a key to 10 species of the genus Lemba Huang, 1983, namely Lemba wushanensis sp. nov. is described in this paper from China. The new species is similar to L. sichuanensis Ma et al, 1994, but differs from the latter by the length of tegmen 2.7 times width in male, length of interspace of mesosternum 3.5 times width in male, posterior margin of epiproct straight; ancorae of epiphallus not inward tilt and vertical diameter 1.8 times subocular furrow in female. The type specimens are deposited in the Northwest Plateau Institute of Biology, Chinese Academy of Sciences, Xining, China.